PENGARUH PENGAJARAN PENDIDIKAN AGAMA KRISTEN TERHADAP PERILAKU PESERTA DIDIK - budiman, Andri; Sianturi, Tumpak OP (Voice of HAMI: Jurnal Teologi dan Pendidikan Agama Kristen, 2022)
Christian Religious Education is an education that is based on the Bible/God's Word, which is very important for the life of a believer. Where through this teaching, it can bring someone to understand and gain an understanding of God and how one can know God's will in human life. PAK teaching in schools is very important, because PAK teaching contains life values that make people recognize and take actions that are in accordance with applicable norms. Without true teaching, humans will live more selfishly. Therefore, the researchers conducted a study at SDN No 076708 Gomo, South Nias Regency, to see if there was an influence of PAK teaching on the behavior of students at SDN No 076708 Tanonikoo Gomo, South Nias Regency, with quantitative research methods. The tool used is a questionnaire in the form of a closed questionnaire. From the research that has been done, it was found that the average value of PAK Teaching at SDN No 076708 Gomo, South Nias Regency. While the value of student behavior is 77.37. The influence of PAK Teaching on Student Behavior 0.402 is very low. The contribution of the influence is 16.16%.